The Effect of Cardiac Rehabilitation on Quality of Life And Functional Capacity in Patients with Heart Failure with Reduced Ejection Fraction: A Systematic Literature Review - Andry Dimas Dwiputra; Bayu Setia (Universitas Malahayati, 2026)
ABSTRACT Heart failure with reduced ejection fraction is a complex clinical syndrome that results in a significant decline in patients’ quality of life and functional capacity. Cardiac rehabilitation has been recognized as a comprehensive evidence-based intervention to address these issues. Objective: To systematically analyze the effect of cardiac rehabilitation on quality of life and functional capacity in patients with heart failure with reduced ejection fraction based on the latest literature. Methods: A systematic literature review was conducted using the PRISMA 2020 guidelines with searches performed in five major electronic databases for the publication period 2021–2025. The inclusion criteria comprised randomized controlled trials and quasi-experimental studies that evaluated the effectiveness of cardiac rehabilitation in adult patients with clinically stable HFrEF. Results: Thirty studies met the inclusion criteria with a total population of 84,064 patients. Cardiac rehabilitation showed a significant improvement in the KCCQ score with a mean increase of 18.4 points and a reduction in the MLHFQ score by 15.8 points. Functional capacity improved with an increase in peak VO2 of 3.2 mL/kg/min and an increase in 6MWT distance of 68.4 meters. Comprehensive programs showed a superior effect size compared to exercise-only interventions. Conclusion: Cardiac rehabilitation provides a clinically significant positive impact on the quality of life and functional capacity of patients with HFrEF, supporting its implementation as a standard of care with a comprehensive and individualized approach. Keywords: Cardiac Rehabilitation, Heart Failure, Quality of Life, Functional Capacity, Systematic Review.